A comprehensive review of current developments on the waste-reinforced polymer-matrix composites for automotive, sports goods and construction applications: Materials, processes and properties. (2020) - Sharma, Shubham; Sudhakara, P.; Misra, S.K.; Singh, Jujhar
Abstract: In recent times, the world is changing and gearing up with latest and new technologies in that scenario the development and growth of the composite materials is increasing day by day. Natural fibres are one of the realistic and ecological alternatives to synthetic fibres as reinforcement for polymer composite materials due to their low cost, environmental friendliness, natural abundance, and mechanical properties. Natural fibres are given first priority compared all types of fibres because of their attractive characteristics such as biodegradable nature, low cost, ecofriendly and good strength to weight ratio in the engineering products and minimal health hazards. An overview on the recent trends in the physio-mechanical properties, thermal properties, electrical properties such as dielectric constant, microstructural interfacial adhesion, different methods used for the fabrication of the natural fiber polymer composites and their respective applications of NFPC's has been discussed thoroughly in this critical review. According to the literature survey, the various work has carried out on the natural fibers which shows its importance comparatively with the other synthetic fibers. This review states the potential of natural fibre which can be used to reinforce the polymer matrix for several applications such as sports goods, electrical and electronics, automotive, construction industry etc.